Little Evidence That Time in Child Care Causes Externalizing Problems During Early Childhood in Norway. Issue 4 (11th January 2013) - Zachrisson, Henrik D.; Dearing, Eric; Lekhal, Ratib; Toppelberg, Claudio O.
<x xml:space="preserve">Abstract</x> Associations between maternal reports of hours in child care and children's externalizing problems at 18 and 36 months of age were examined in a population‐based Norwegian sample (n = 75, 271). Within a sociopolitical context of homogenously high‐quality child care, there was little evidence that high quantity of care causes externalizing problems. Using conventional approaches to handling selection bias and listwise deletion for substantial attrition in this sample, more hours in care predicted higher problem levels, yet with small effect sizes. The finding, however, was not robust to using multiple imputation for missing values. Moreover, when sibling and individual fixed‐effects models for handling selection bias were used, no relation between hours and problems was evident.